Comparison of knowledge and attitudes about antibiotics and resistance, and antibiotics self-practicing between Bachelor of Pharmacy and Doctor of Pharmacy students in Southern India - Ahmad, Akram; U. Khan, Muhammad; Moorthy, Jagadeesan; Jamshed, Shazia Qasim; Patel, Isha (Grupo de Investigacion en Atencion Farmaceutica, 2015)
BACKGROUND: There is limited research on pharmacy specialization based differences with regards to usage of antibiotics. OBJECTIVE: To compare the knowledge, attitude and practice of Bachelor of Pharmacy (BPharm) and Doctor of Pharmacy (PharmD) students about usage and resistance of antibiotics in Southern India. METHODS: This was a cross sectional study involving final year BPharm and PharmD students studying in two private institutions located in Andra Pradesh, India. The study was conducted for the period of 3 months. The questionnaire was divided into 5 components: demographics, knowledge about antibiotic use, attitude towards antibiotic use and resistance, self-antibiotic usage, and possible causes of antibiotic resistance. The study questionnaire was assessed for reliability. Data were analysed by employing Mann Whitney and chi square tests using SPSS version 19. RESULTS: The sample size comprised of 137 students. The response rate was 76.11% for the study. There was a significant difference in the knowledge of antibiotic use in BPharm and PharmD students (Mean score: 5.09 vs 6.18, p<0.001). The overall attitude of PharmD students about antibiotic use and resistance was positive compared to BPharm students (Mean score: 3.05 vs 2.23, p<0.05). The self-antibiotic practices was higher in BPharm students than PharmD students (36.4% vs 20%, p<0.05). A significantly high number of PharmD students believed that empirical antibiotic therapy led to antibiotic resistance (19.5% versus 48%, P<0.05). CONCLUSION: PharmD students were more knowledgeable about antibiotic usage and resistance compared to BPharm students who did not have accurate and the much needed information about the same. Future interventions should be targeted towards educating the BPharm students so that they can implement the acquired knowledge in their practice.